Urbanidade e Justiça Espacial na cidade de São Paulo: metodologia de análise e subsídio para tomada de decisão no planejamento urbano - Katia Canova (Confins)
This research aims to assess the use of scientific methodologies in building a dialogue with technical analysis for urban planning in public agencies. Or even more objectively, to explore the use of a Geographic Information System - GIS, combined with the Hierarchical Analysis Method, guided by the conceptual formulation called urbanity, complemented by the idea of ​​spatial justice, in the context regulatory frameworks, to support decision-making in public investment in urban planning in the municipality of São Paulo. It takes as its axis of study the public spaces, the uses and perceptions that are made there, analyzed on a human scale. It uses elements of historical cartography, centered on the history of town planning and photographs, with the aim of defining qualitative indicators of appropriation and transformation of spaces in current use over time. It works with the methodology proposed in three approach scales, providing a case study for each scale. It is based on an exercise carried out in the city of Lyon, exploring the universality of the methodology. We present an applied case study (choice of territorial units best able to receive the 3rd phase of the Programa Centro Aberto da SPUrbanismo program, a comparative analysis of four places in the city of Lyon, and the composition of a benchmark index for decision-making, based on urbanity and spatial justice for the city of São Paulo. Mapping is present in research in all its phases, whether it presents the map as an element providing historical data, or as a public good (composer of right) or as a means of analysis, investigation and data processing to support town planning decisions.